Transcriptomics and metabolomics reveal the molecular and metabolic adaptation to heat stress in Manila clam Ruditapes philippinarum - Jing, Hao; Zhou, Liqing; Gao, Yiqiang; Liu, Zhihong; Wu, Biao; Sun, Xiujun; Tu, Kang (Frontiers in Marine Science, 2023)
Temperature is an important environmental factor affecting metabolism, growth and life activities of marine bivalves. To reveal the molecular and metabolic responses to heat stress, comparative transcriptomics and metabolomics were performed in the commercially important bivalve, Manila clam Ruditapes philippinarum. Comparative transcriptomics revealed a total of 3980 differential genes (DEGs) mainly involved in energy metabolism, protein processing, glycerolphospholipid metabolism, inoxidizability and anti-apoptosis. Comparative metabolomic analysis identified 293 differential metabolites (DEMs) in the heat-stressed clams, including Acetyl-CoA, Beta-D-Glucose, phosphatidylcholine and free amino acids. For the heat-stress clams, they showed the significantly increased enzyme activities of AKP and ACP, as well as antioxidant-related enzyme activities (SOD and CAT) and oxidative damage substance (MDA). The changes in gene expression of glycolysis-related genes (GLUT1, GLK, HK1 and GPI6) and metabolites (Beta-D-Glucose and Acetyl-CoA) reflect the adjusted energy metabolism in the heat-stressed clams. The protein processing in endoplasmic reticulum may play the important roles in the stability of cell membrane structure during heat adaptation. The increased contents of glycerophospholipid (PC) may be essential to maintain the stability and permeability of cell membrane in the heat-stressed clams. Molecular chaperones (HSP70 and HSP90) may participate in the degradation of misfolded proteins to maintain cell homeostasis during the heat stress. To defense the heat stress, clams also initiate the protection and defense mechanisms by activating antioxidant system, innate immune system and anti-apoptotic system. These findings will shed new lights on molecular and metabolic adaptation to heat stress in the intertidal mollusks in a warming climate at the global scale.